Effect of oocyte in vitro maturation interval on subsequent ICSI embryo quality and development - Rodríguez, M. B. (2018)
Fil: Rodríguez, M. B. Universidad de Buenos Aires. Facultad de Agronomía. Laboratorio de Biotecnología Animal; Argentina